2020
DOI: 10.1002/adfm.202005462
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Co‐Crystallization of Halogenated Non‐Fullerene Acceptors for Thermally Stable Ternary Solar Cells

Abstract: While photovoltaic blends based on non-fullerene acceptors are touted for their thermal stability, this type of acceptor tends to crystallize, which can result in a gradual decrease in photovoltaic performance and affects the reproducibility of the devices. Two halogenated indacenodithienothiophene-based acceptors that readily co-crystallize upon mixing are studied, which indicates that the use of an acceptor mixture alone does not guarantee the formation of a disordered mixture. The addition of the donor poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
2
46
0
1
Order By: Relevance
“…57 Ternary OPV blends, which offer a series of long-term stability and performance advantages over the classical binary bulk heterojunctions, 71 have also been effectively screened by means of compositional libraries realized by blade coating. 27,72 In this case, a layer-by-layer strategy was employed to subsequently deposit, one on top of the other, the different layers of the constituent active layer materials. Depending on the layer ordering and velocity profile employed (either constant speed or acceleration), complementary areas of the ternary diagram are covered, so that less than 5 combinatorial samples are required to explore a significant fraction of the ternary phase diagram.…”
Section: Solution-processed High-throughput and Combinatorial Librariesmentioning
confidence: 99%
“…57 Ternary OPV blends, which offer a series of long-term stability and performance advantages over the classical binary bulk heterojunctions, 71 have also been effectively screened by means of compositional libraries realized by blade coating. 27,72 In this case, a layer-by-layer strategy was employed to subsequently deposit, one on top of the other, the different layers of the constituent active layer materials. Depending on the layer ordering and velocity profile employed (either constant speed or acceleration), complementary areas of the ternary diagram are covered, so that less than 5 combinatorial samples are required to explore a significant fraction of the ternary phase diagram.…”
Section: Solution-processed High-throughput and Combinatorial Librariesmentioning
confidence: 99%
“…Here, we cite other reports where the optimized ternary blend showed reduced crystallinity compared with the binary configuration. [ 96,108,109 ]…”
Section: Global Morphologymentioning
confidence: 99%
“…Many studies have shown that the addition of a third component can circumvent this issue, leading to more optimal sized domains and improved morphological stability. [ 97,108,119–121 ]…”
Section: Global Morphologymentioning
confidence: 99%
See 2 more Smart Citations